TRANSFORMASI PEMBELAJARAN PJOK MELALUI AKTIVITAS GERAK: DAMPAKNYA TERHADAP KEMAMPUAN NUMERASI DAN KETERAMPILAN GERAK SISWA - Yulian Valid Handhana, Rizki; Nur Muhammad , Heryanto; Hidayat, Taufiq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the impact of transforming Physical Education, Sports, and Health (PJOK) instruction through movement activities on the numeracy and movement skills of elementary school students. A quantitative approach was employed using a quasi-experimental method with a One-Group Pretest-Posttest Design. The study sample consisted of 36 students. Research instruments included a numeracy test and a movement skills test (TGMD-2). Data were analyzed using normality tests, paired sample tests, and N-Gain tests. Shapiro-Wilk normality test results indicated that the data for numeracy skills (pretest p = 0.071; posttest p = 0.062) and fundamental movement skills (pretest p = 0.120; posttest p = 0.490) were normally distributed (p > 0.05), thereby satisfying the assumptions for parametric analysis. Furthermore, paired sample test results revealed significant differences between pretest and posttest scores for both numeracy and fundamental movement skills (p = 0.000 < 0.05). The magnitude of the improvement in learning outcomes was analyzed using the N-Gain test. Results showed N-Gain values ​​of 0.51 for numeracy skills and 0.58 for fundamental movement skills; both values ​​fall into the moderate category. These findings indicate that integrating movement activities into PJOK instruction has an impact on numeracy and fundamental movement skills.